2001
DOI: 10.1007/bf03028317
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved spectroscopy (NIRO-300) does not agree with jugular bulb oxygen saturation in patients undergoing warm bypass surgery

Abstract: Spatially troscopy does not resolved spec-(NIRO-300) agree with jugular bulb oxygen saturation in patients undergoing warm bypass surgery Purpose: Near infrared spectroscopy (NIRS) is a promising noninvasive method for continuous monitoring of cerebral oxygenation during cardiac surgery with cardiopulmonary bypass (CPB). This study was designed to study the agreement between tissue oxygen index (TO o measured by spatially resolved spectroscopy (NIRO-300) and jugular bulb oxygen saturation (SjO2) in patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…This seems to be an important issue, when NIRS tissue oxygenation is compared with oxygen saturation in the venous outflow of a specific organ or vascular region. 26 Third, it should be kept in mind that, in cyanotic cardiac patients, adaptive mechanisms regarding splanchnic blood flow and oxygen extraction may affect distribution of blood in the liver and may, therefore, be a contributing factor. Fourth, the fact that TOI was greatly influenced by systemic variables, such as arterial oxygen saturation, vascular resistances and, to a lesser extent, by inferior caval SO 2 and cardiac output, implies that the NIRS method used reflects global tissue oxygenation rather than tissue oxygenation in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…This seems to be an important issue, when NIRS tissue oxygenation is compared with oxygen saturation in the venous outflow of a specific organ or vascular region. 26 Third, it should be kept in mind that, in cyanotic cardiac patients, adaptive mechanisms regarding splanchnic blood flow and oxygen extraction may affect distribution of blood in the liver and may, therefore, be a contributing factor. Fourth, the fact that TOI was greatly influenced by systemic variables, such as arterial oxygen saturation, vascular resistances and, to a lesser extent, by inferior caval SO 2 and cardiac output, implies that the NIRS method used reflects global tissue oxygenation rather than tissue oxygenation in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…While Kadoi et al 34 found that NIRS was more effective in detecting brain desaturation than SjVO 2 at certain stages of normothermic and hypothermic CABG and suggested that one should not rely solely on SjVO 2 during cardiopulmonary bypass (CPB), others 24,27,48 considered NIRS less sensitive than SjVO 2 . The sole randomized controlled trial 63 performed did not ascertain any difference in the number of neurological complications between patients who underwent NIRS monitoring and those who did not.…”
Section: Clinical Efficacy Of Nirs In Heart Surgerymentioning
confidence: 99%
“…However, it does have obvious limitations [2][3][4]; it detects regional cerebral oxygenation (small area under the optodes), the optical path length is difficult to quantify, and arterial and venous changes are not distinguished. The previous limitations were very clear in adult studies [2,4,5]. Indeed, our group [5] reported a significant bias with wide limits of agreement between jugular bulb oxygen saturation and tissue oxygen index monitored by NIRO 300 in adult patients undergoing coronary bypass surgery.…”
Section: A Replymentioning
confidence: 87%
“…There is no doubt that more work is needed in this field and we thank the correspondents for their suggestions. .............................................................................................................................................................................................................. [4] and jugular venous [5] saturations in individuals, but the relationship is variable and inconsistent between subjects. In addition a number of methodological problems have been identified with NIRS including attenuation of the infrared signal by extracerebral tissues [6], and variability between devices [7].…”
mentioning
confidence: 99%